Influence of moderate electric fields in β-lactoglobulin thermal unfolding and interactions. (30th January 2020) - Rodrigues, Rui M.; Avelar, Zita; Vicente, António A.; Petersen, Steffen B.; Pereira, Ricardo N.
Abstract: In this study, the effects of moderate electric fields during thermal denaturation of β-lactoglobulin were examined through an in situ circular dichroism approach, complemented by intrinsic extrinsic fluorescence analysis. Results have shown that the effects of electric fields in protein unfolding were linearly dependent on the applied electric field intensity (V/cm) and increased by the use of low electric frequencies – i.e. 50 to 200 Hz. These electric effects caused significant changes on β-lactoglobulin melting temperature, unfolded conformation and subsequent intermolecular interactions, revealed by the increase of surface hydrophobicity (ANS affinity) and higher conservation of retinol binding. The obtained data provides a clear evidence that moderate electric fields contribute to distinct folding/unfolding of β-lactoglobulin, resulting in structural modifications. These findings are relevant for (bio)-technological applications involving electric fields processing, bringing new insights for the development of innovative strategies to control protein function and tune production of functional protein systems. Highlights: Thermal unfolding of β-lactoglobulin was affected by moderate electric field processing. Structural changes of β-lactoglobulin were assessed by an in situ circular dichroism analysis. Moderate electric fields change protein structure and subsequent molecular interactions. Structural changes were dependent of electric field strength and frequency.